PENINGKATAN PENGETAHUAN DAN KETERAMPILAN KADER POSYANDU MELALUI DEMONSTRASI PIJAT BAYI DI WILAYAH PUSKESMAS UJANMAS KABUPATEN MUARA ENIM - khairunisya khairunisya; ekadewi retnosari; nia clarasari MP; dahliana dahliana; siti fatimah (J-KESMAS: Jurnal Kesehatan Masyarakat, 2024)
AbstractBaby massage has been proven to have benefits for mothers. Cadres play a role in postpartum including training in baby massage. This research aims to determine baby massage training for cadres to increase the knowledge and skills of health cadres in the Ujanmas Community Health Center working area. This research uses a quasi-experiment design with a pre-post test without control approach. The subjects of this research were active cadres in the working area of the Ujanmas Health Center, Muara Enim Regency, South Sumatra. The research was carried out in September – December 2023. The sample size was measured using the difference between two means test, which resulted in 30 participants being randomly assigned to groups. Statistical tests use the Wilcoxon rank test. The results showed that cadres' knowledge before the intervention was 34.31 ± 7.82 and after the intervention their knowledge increased to 81.80 ± 10.2. Cadre skills before the intervention were 18.01 ± 4.5 and after the intervention increased to 88.21 ± 17.2. The results of the statistical test were positive (p value 0.000 <0.05). This could mean that baby massage training for cadres has an effect on increasing cadres' knowledge and skills in baby massage in the Ujanmas health center working area. Cadre training can increase knowledge and skills in baby massage so that they can be passed on to postpartum mothers to massage their babies properly.